Peran Pembayaran Digital Payment Gateway Dalam Meningkatkan Kinerja Keuangan Pada UMKM - Angelia Alfatwa Rusandi Siregar; Heny Triastuti Kurnia Ningsih; Pretty Nur A’yuni Laoli (CiDEA Journal, 2023)
The emergence of the term Financial Technology (fintech) today is one of the changes caused by current developments. Financial technology (fintech) has several types, one of which is payment gateway. Currently, MSMEs in Indonesia have an important role in Indonesia, namely improving its economy and being able to accelerate regional development. The aim of this research is how influential the use of digital payment "payment gateways" is in improving the financial performance of MSMEs, through the findings and views of previous researchers. The method used is the Systematic Literature Review (SLR) method, which aims to find out the results of previous research related to this research. The results of this research show that digital payments "payment gateway" have a positive effect on improving the financial performance of MSMEs.